STIGLER’S INFLUENTIAL CONTRIBUTION TO ECONOMIC THOUGHT - Artidiatun Adji (Journal of Indonesian Economy and Business (JIEB), 2017)
This paper analyzes George J. Stigler’s influential contributions to economic ideas, specifically on industrial structures, the functioning of markets, the causes and effects of public regulation, the economics of information, and on the development of economic thought. Stigler’s most influential contribution to economic thought came in his work on information theory. Treating information as a valuable commodity, he explained why prices differ for identical goods. From his work, many other theories have been built to explain economic behavior. A considerable number of works on decision making under uncertainty could not have progressed without an understanding of the role of information. His swing of the pendulum in economic regulation constitutes a great turnabout. He started research, known as public choice, which assumes that government policy makers are driven by self-interest rather than pure concern for the public’s welfare. His views have now become those of  the mainstream.